1998
DOI: 10.1159/000013315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Diabetes on Blood Flow Rate and Primary Outcome of Newly Created Hemodialysis Arteriovenous Fistulas

Abstract: To study the feasibility of creating a radiocephalic hemodialysis fistula in elderly and diabetic patients, we prospectively studied 176 patients undergoing the first permanent vascular access creation and followed the outcome of fistula until primary failure or success was assessed. Color duplex ultrasonography was used to measure the blood flow rate. Fistula blood flow rate was significantly smaller in elderly patients, however, it was >400 ml/min in over 78% of the elderly patients with successful fistulas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 14 publications
6
80
1
3
Order By: Relevance
“…Various studies have documented that the increments in blood flow begin to occur soon after the construction of an AVF in a great majority of cases (6,(12)(13)(14)(15)(16)(17)(18)(19) (Figure 2A). A recent report demonstrated changes in blood flow in an AVF after its construction (6).…”
Section: Timing Of Changes In Blood Flow and Diameter In A Newly Creamentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have documented that the increments in blood flow begin to occur soon after the construction of an AVF in a great majority of cases (6,(12)(13)(14)(15)(16)(17)(18)(19) (Figure 2A). A recent report demonstrated changes in blood flow in an AVF after its construction (6).…”
Section: Timing Of Changes In Blood Flow and Diameter In A Newly Creamentioning
confidence: 99%
“…Although mechanisms of AVF maturation are complex and the exact timing of maturation is difficult to pinpoint, ample information exists in the literature regarding the general process (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Nevertheless, the phenomenon remains poorly understood by many nephrologists as well as vascular surgeons.…”
mentioning
confidence: 99%
“…Other factors included gender and diabetes mellitus. However, those factors were not related to the successful maintenance of revised vascular access [22][23][24].…”
Section: Vascular Accessmentioning
confidence: 96%
“…Studies outside the Asian region revealed the overall superiority of upper arm AVF over lower arm AVF, a difference also true for diabetic patients [23]. In a Chinese study which included patients with radiocephalic AVF, age alone did not influence outcomes, but a combination of diabetes mellitus and old age were considered to be complicating factors [24]. Both the use of lower arm AVF and the combination of diabetes mellitus and age could affect fistula outcomes, but there is a lack of data to conclusively support this claim.…”
Section: Vascular Accessmentioning
confidence: 99%
“…É a via permanente de maior durabilidade e segurança, realizada preferencialmente em regiões distais dos membros superiores a fim de permitir ao paciente maior liberdade de movimento durante a hemodiálise e nos afazeres cotidianos (LIMA, 2000). É necessário um período de quatro a oito semanas para que a FAV possa ser utilizada, considerando que neste período ocorre o espessamento da parede dos vasos e a dilatação do ramo venoso que permitirá a inserção repetida das agulhas de punções para a hemodiálise (LIN et al, 1998;IKEDA;BESARAB;RAJA, 2003).…”
Section: Introductionunclassified